A multidimensional framework for cloud adoption of SMEs in India. (28th February 2020) - Shetty, Jayalaxmi P.; Panda, Rajesh
The purpose of this article is to develop an integrated, multidimensional and theory-driven conceptual model from established technology adoption theories. Owing to a dissimilar set of factors influencing the process, under same market conditions, the adoption process calls for a comprehensive understanding of the determinants of cloud adoption. The research accounts for the intricacy and idiosyncrasy of Indian SME practice. Building on interpretive research, the article links the antecedents of cloud adoption and the consequences of field data to capture 12 significant factors. Interestingly, field data reveal critical components that were specific to cloud service providers, namely trust, data residency, and offline function. Cumulatively, the conceptual outlook of the model discusses the following; significant factors to guide Indian SMEs towards cloud adoption, economic performance as an impact of cloud adoption and pointers for cloud service providers to deal effectively with the business ecosystem of the SMEs.